2020
DOI: 10.15381/rivep.v31i1.17571
|View full text |Cite
|
Sign up to set email alerts
|

El intervalo de tiempo entre la estimulación ovárica con FSH/LH y la colecta afecta la cantidad, calidad y capacidad de desarrollo de los ovocitos recuperados de novillas criollas ecuatorianas

Abstract: El objetivo del estudio fue evaluar los efectos del tratamiento con gonadotropina y el intervalo entre la estimulación ovárica con FSH/LH y la sesión de aspiración folicular, sobre la cantidad y calidad de los complejos cúmulus ovocitos (COCs) obtenidos por ovum pick up (OPU) en vaquillas criollas ecuatorianas. Cuatro novillas fueron asignadas aleatoriamente a cuatro grupos (FHS/LH 40h; FSH/LH 48h; control 40h; control 48h). En dos grupos se aplicó una dosis (0.011 mg, IM) de GnRH el día 0, seguida de 500 UI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Results of different studies showed that crosses and Scandinavian red breeds had better fertility than pure Holstein breed (Heins et al, 2006;Aguilar et al, 2018). This performance in native cattle could increase circulating glucose concentrations (Leane et al, 2018), which are positively associated with ovulation rates and in vivo follicular growth and, therefore, with a greater number of transferable embryos (Guanga et al, 2020;Laskowski et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Results of different studies showed that crosses and Scandinavian red breeds had better fertility than pure Holstein breed (Heins et al, 2006;Aguilar et al, 2018). This performance in native cattle could increase circulating glucose concentrations (Leane et al, 2018), which are positively associated with ovulation rates and in vivo follicular growth and, therefore, with a greater number of transferable embryos (Guanga et al, 2020;Laskowski et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Following this recommendation, creole bull semen has been successfully cryopreserved (Argudo et al, 2019). Also, attempts have been made to boost in vitro embryo production (IVP) in creole cows through in vitro maturation (Ayala et al, 2018(Ayala et al, , 2020Alvarado et al, 2020), in vitro culture (Méndez et al, 2019) and vitrification of oocytes recovered by transvaginal ultrasoundguided follicular aspiration (Méndez et al, 2020). However, the entire IVP process as well as the cryotolerance of creole embryos (e.g., to vitrification/warming) need to be investigated further.…”
Section: Introductionmentioning
confidence: 99%